Collagenofibrotic glomerulopathy - A rare disease diagnosed with the aid of transmission electron microscopy - Smita Mary Matthai; Anjali Mohapatra; Neelaveni Duhli; Vinoi G David; Santosh Varughese (Wolters Kluwer Medknow Publications, 2020)
Collagenofibrotic glomerulopathy (CFG) is a rare idiopathic kidney disease characterized by abnormal deposition of atypical Type III collagen fibers in the glomerulus causing subendothelial and mesangial expansion, manifesting as progressive renal dysfunction accompanied by proteinuria. The majority of CFG cases reported in literature are from Japan where this disease entity was initially recognized. There is an increased awareness and diagnosis of this rare renal disease in India with the recent increase in utilization of electron microscopy (EM) in clinical diagnostic settings. We describe a 28-year-old Bangladeshi woman who presented with hypertension and nephrotic range proteinuria not amenable to treatment with steroids and cyclophosphamide, whose renal biopsy demonstrated diagnostic ultrastructural features of CFG. This illustrative case is presented to highlight the role of EM analysis for diagnostic accuracy in renal biopsy evaluation in addition to demonstrating the unusual renal biopsy findings of this rare entity.